Pengaruh Brand Image, Kualitas Pelayanan, dan Keragaman Produk terhadap Keputusan Pembelian di Rumah Madumongso - Adelia Kusuma; Ustadus Sholihin; Iing Sri Hardiningrum (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The souvenir industry in Kediri has become increasingly competitive, driving business actors to strengthen their marketing strategies through brand image, service quality, and product variety. Rumah Madumongso, as one of the well-known local souvenir centers, faces challenges in maintaining consumer appeal amid the abundance of similar products available in the market. Therefore, a study is needed to examine the factors influencing consumer purchasing decisions. This research aims to analyze the influence of brand image, service quality, and product variety on purchasing decisions, both partially and simultaneously. The study applied a quantitative approach with a survey method, collecting data from 130 respondents using questionnaires distributed through accidental sampling. Data analysis was conducted using SPSS, employing validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results show that brand image and product variety have a positive but not significant effect on purchasing decisions. In contrast, service quality has a positive and significant influence, emphasizing the crucial role of service in encouraging consumers to make purchases. Simultaneously, the three variables significantly influence purchasing decisions, as indicated by an F-value of 56.740 with a significance level of 0.000. The coefficient of determination (R²) of 0.575 indicates that 57.5% of the variation in purchasing decisions is explained by brand image, service quality, and product variety, while the remaining 42.5% is influenced by other factors beyond this study. These findings highlight the need for more comprehensive marketing strategies to strengthen the competitiveness of local souvenir industries.